2016
DOI: 10.1080/00913847.2016.1148561
|View full text |Cite
|
Sign up to set email alerts
|

The influence of medial patellofemoral ligament reconstruction on clinical results and sports activity level

Abstract: Patellar stabilization with MPFL reconstruction is a safe and effective treatment method for all patients with patellofemoral instability and allows most patients to return to regular physical and sports activities after surgical intervention. Although sports activity level increased significantly after surgery, the same level of sports activity before the patellar dislocation has not been achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 54 publications
1
19
0
1
Order By: Relevance
“…Nonanatomical and anatomical techniques are well described previously. [4][5][6][7][18][19][20] Nonanatomical surgical techniques alter the premorbid patella mechanics by several principles. Biomechanical studies have demonstrated that the length change pattern of a MPFL reconstruction depends critically on the attachment site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonanatomical and anatomical techniques are well described previously. [4][5][6][7][18][19][20] Nonanatomical surgical techniques alter the premorbid patella mechanics by several principles. Biomechanical studies have demonstrated that the length change pattern of a MPFL reconstruction depends critically on the attachment site.…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective study, 68 patients with patellar instability were evaluated before and after surgical treatment, which was performed from May 2005 to February 2010. They included 22 male and 46 female patients with a mean age of 21 years (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) at first admission. Median duration of preoperative patellar instability was 12 months (range from 6 months to 3 years).…”
Section: Patientsmentioning
confidence: 99%
“…A review by Matic et al [21] about the return-to-sport rates in a heterogeneous sample with combined MPFL reconstruction, MPFL repair, and patients with medial retinaculur repair/plication reported a return-to-sport rate to the previous sport level of 90%. Ambrozic et al described returns to sport in 88.5% of patients following MPFL reconstruction; 69.6% of patients returned to the same level [22]. Also, Lippacher et al [23] reported similar return-to-sport rates after isolated MPFL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple studies have reported rates at which athletes return to their preinjury level (53%-69.6%) after MPFL reconstruction, but they do not evaluate objective criteria before releasing patients to return to play. 3,35 In a previous systematic review published in 2010, Fisher et al 24 reported that while MPFL reconstruction showed excellent functional results, there was little known about whether this surgical intervention enabled patients to safely return to sports. As MPFL reconstruction techniques have evolved rapidly in recent years, we aimed to identify whether objective criteria have been identified to allow athletes to safely return to play to minimize reinjuries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, multiple studies have reported rates at which athletes return to their preinjury level (53%-69.6%) after MPFL reconstruction, but they do not evaluate objective criteria before releasing patients to return to play. 3,35…”
Section: Discussionmentioning
confidence: 99%